Recomposition and storage of sunlight with intelligent phosphors for enhanced photosynthesis. Issue 32 (9th August 2021) - Zhang, Zhijun; Han, Qinyu; Liu, Songhan; Wang, Zhimin; Hu, Ming; Domnic, Szeto Mun Wai; Lau, Raymond; Xing, Bengang
Abstract : This work presents a smart solar energy regulation strategy using photon tunable long persistent phosphors as solar energy harvesting antennas to enhance overall sunlight utilization by photosynthetic organisms in multiple modes. Abstract : This work presents a smart solar energy regulation strategy using photon tunable long persistent phosphors as solar energy harvesting antennas to enhance overall sunlight utilization by photosynthetic organisms in multiple modes.